CCR9 Antagonists in the Treatment of Ulcerative Colitis - Pirow Bekker; Karen Ebsworth; Matthew J. Walters; Robert D. Berahovich; Linda S. Ertl; Trevor T. Charvat; Sreenivas Punna; Jay P. Powers; James J. Campbell; Timothy J. Sullivan; Juan C. Jaen; Thomas J. Schall (Mediators of Inflammation)
While it has long been established that the chemokine receptor CCR9 and its ligand CCL25 are essential for the movement of leukocytes into the small intestine and the development of small-intestinal inflammation, the role of this chemokine-receptor pair in colonic inflammation is not clear. Toward this end, we compared colonic CCL25 protein levels in healthy individuals to those in patients with ulcerative colitis. In addition, we determined the effect of CCR9 pharmacological inhibition in the mdr1a−/− mouse model of ulcerative colitis. Colon samples from patients with ulcerative colitis had significantly higher levels of CCL25 protein compared to healthy controls, a finding mirrored in the mdr1a−/− mice. In the mdr1a−/− mice, CCR9 antagonists significantly decreased the extent of wasting and colonic remodeling and reduced the levels of inflammatory cytokines in the colon. These findings indicate that the CCR9:CCL25 pair plays a causative role in ulcerative colitis and suggest that CCR9 antagonists will provide a therapeutic benefit in patients with colonic inflammation.